Трансформація соціальної структури сільського населення України в 1991-2012 рр. - Федоренко, Яніна Анатоліївна; Fedorenko, Yanina A. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Статтю присвячено аналізу трансформаційних процесів соціальної структури сільського населення, які відбулися протягом такого історичного відтинку часу як період незалежності. Зокрема, характеризується чисельність, склад та територіальне розміщення сільського населення, досліджуються процеси народжуваності і смертності, як невід’ємні складові демографічної картини соціальної структури селянства. На основі поданого матеріалу формулюються висновки про етапи трансформацій соціальної структури українського села. The article is devoted to the analysis of transformation processes of villagers' social structure during the Independence period. The author researches ,in particular, population size, structure and territotorial the location of the rural population, birth and death processes as an integral part of the demographic picture of rural population structure. The conclusions are made on the basis of the studied materials as to the stages of transformation processes of villagers' social structure:1991 - 2001 - I stage (rapid decrease of rural population, deterioration of age and sex structure of various social categories, increase of total death indications together with rapid fall in birth ).2002-2012 - II stage of transformational changes (stabilization of demographics in Ukraine).
Transformation of Ukrainian Villagers' Social Structure in 1991-2012
Keywords: українське село; демографічний стан; народжуваність; смертність; депопуляція; Ukrainian village; demographic state; fertility; mortality; depopulation